تقييم الطرق المتبعة من قبل الأمهات بكيفية تحضير وجبة الحليب الصناعي للرضع: Evaluation of the methods used by mothers on how to prepare an artificial milk meal for infants - عزة المعتمد عمار ابراهيم الورفلي; خالد الهادي ابراهيم شكشك (Surman Journal of Science and Technology, 2025)
The current study aimed at evaluating the methods used by the mothers, with how to prepare the milk and industrial meal for infants, and to study the relationship between sterilization methods, and among the variables there is also the relationship between the child’s infection with bacteria due to the knowledge of the application of instructions and instructions and the extent to which the mother applies the instructions and the correct tips. It was 60 forms, and distributed in the pediatric department, the synecology department, the neonatal department in Sabratah Teaching Hospital, where the data was collected and the statistical methods was used (2010 Microsoft Excel) in statistical analysis. The results showed that by distributing the sample according to the job, the highest percentage was 33% for house wives, followed by female employees, and it reached 30%, it is clear from the distribution of the sample that the highest rate of breast – feeding baby, and it was 52%. According to cleaning methods. The highest percentage of lactation was the water lactation of the lactation with cold water, and it amounted to 53%. Most of the sample members do not apply the instructions and instructions on the milk carton: the dryer, where the percentage reached 92%, and a large percentage of the sample members had a diarrhea and sensitivity and the percentage was 70%.